2012
DOI: 10.1111/j.1523-1739.2012.01823.x
|View full text |Cite
|
Sign up to set email alerts
|

Feedbacks between Conservation and Social‐Ecological Systems

Abstract: Robust ways to meet objectives of environmental conservation and social and economic development remain elusive. This struggle may in part be related to insufficient understanding of the feedbacks between conservation initiatives and social-ecological systems, specifically, the ways in which conservation initiatives result in social changes that have secondary effects on the environments targeted by conservation. To explore this idea we sampled peer-reviewed articles addressing the social and environmental dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 49 publications
1
62
0
Order By: Relevance
“…However, these labels are rarely discussed or unpacked. The challenges to be overcome are more often discussed and explored in terms of inherent difficulties such as those associated with adopting systemic approaches (e.g., Miller et al 2012) or promoting stakeholder involvement (Reed 2008). While these may indeed be inherently difficult, perhaps because they entail greater complexity, challenges may also arise simply because they are new and differ from prior ways of working (Harries andPenning-Rowsell 2011, Rogers et al 2013).…”
Section: Rationale For Studying Legacy Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these labels are rarely discussed or unpacked. The challenges to be overcome are more often discussed and explored in terms of inherent difficulties such as those associated with adopting systemic approaches (e.g., Miller et al 2012) or promoting stakeholder involvement (Reed 2008). While these may indeed be inherently difficult, perhaps because they entail greater complexity, challenges may also arise simply because they are new and differ from prior ways of working (Harries andPenning-Rowsell 2011, Rogers et al 2013).…”
Section: Rationale For Studying Legacy Effectsmentioning
confidence: 99%
“…Past top-down and technocratic approaches have been critiqued: In response, a new discourse emphasizes the need to "open up" to more holistic and participatory approaches (Sterling et al 2010, Miller et al 2012. The participation of other interested parties is advocated because involving and incorporating stakeholder views is thought to contribute to more informed, effective, and equitable outcomes (e.g., Reed 2008, Paavola andHubacek 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By the 1980s and 1990s, there was a significant shift in how international conservation organizations planned environmental conservation projects, from a top-down model of simply demarcating a protected area, to one that-at least in rhetoric-aimed to include the people living near proposed protected areas in planning and management processes. 4 In many instances, this "participatory" approach still reproduced top-down initiatives, and scholarly analyses of conservation efforts emphasized how these projects came from an elite environmental ethic, funded by Northern sources, and foisted onto rural populations in various parts of the Global South (e.g., Brockington 2002, Chernela 2005, Grandia 2012, Igoe 2004, Miller et al 2012, NaughtonTreves et al 2005, Neumann 2002). Other recent research in environmental conservation aims to complicate the simple model of global domination, and scholars provide compelling ethnographic detail about how various local constituents are not only affected by, but also engage with conservation efforts (Agrawal 2005, Brosius 1997, Doane 2012, Escobar 2008, Grandia 2012, Haenn 2005, Mathews 2011, Moore 1998, Munster and Munster 2012, Sundberg 2006, West 2006.…”
Section: The Global Dynamic Of Environmental Conservationmentioning
confidence: 99%
“…Jarvis et al (2012:668) argued that feedback links "need to exist between climate change and societal actions" for policymakers to limit carbon dioxide emissions. Miller et al (2012) reviewed the literature on feedbacks between conservation actions and social responses, finding that positive feedbacks have thus far been reported more often than negative feedbacks in social-ecological systems. Miller et al (2012), is in accord with the recent review from Chin et al (2014:38), which found that more "detailed case studies," using interdisciplinary approaches and integrative methods, are needed to enable researchers to build a general understanding of feedbacks in these systems.…”
Section: Introductionmentioning
confidence: 99%